Quality of Life in Painful Peripheral Neuropathies: A Systematic Review - Ayesha Girach; Thomas Henry Julian; Giustino Varrassi; Antonella Paladini; Athina Vadalouka; Panagiotis Zis (Pain Research and Management)
Objective. Neuropathic pain is a common presenting complaint of patients with peripheral neuropathy (PN) and is considered one of the most disabling neuropathic symptoms, with detrimental effects on patients’ quality of life (QoL). The aim of this review was to overview the current literature that focuses on QoL in painful PN of various aetiologies. We sought to clarify the direct effect of pain and its treatment on patients’ QoL. Methodology. A systematic computer-based literature search was conducted using the PubMed database to search for papers on QoL in painful PN. Information was extracted regarding prevalence, demographics, and response to treatment where relevant. Results. We identified 66 articles eligible for inclusion. The vast majority of studies (n=47) focused on patients with diabetic PN. Other aetiologies of painful PN where QoL has been studied to date include gluten, immune-mediated, HIV, chemotherapy-induced, and chronic idiopathic axonal polyneuropathy. Pharmacological treatment is the mainstay in managing pain and has a direct positive and independent effect on the overall QoL. Other nonpharmacological approaches can also be of benefit, either alone or as adjuvant treatments, and are discussed. Conclusion. The findings demonstrate that QoL is impaired in painful PN and should not be neglected in clinical practice. Patients’ pain management and subsequent impact on QoL should routinely be assessed and monitored.